Bacterial Identification of Ornamental Betta Fish (Betta splendens) - Safika Safika; Nazmi Zahir B. Mohd Zaini; Usamah Afif; Agustin Indrawati; Rahmat Hidayat; Titiek Sunartatie (Jurnal Medika Veterinaria, 2023)
Betta fish (Betta splendens) are one of the most popular ornamental fish due to their gorgeous colors and various shapes. This study aimed to find pathogenic bacteria in betta fish (Betta splendens) in fish farm in Bogor. Body swabs were collected from four decorative betta fish, and from tank water. Two of the fish were dead and two of which were exhibiting symptoms of disease. Bacterial isolation was performed on multiple agar media, and bacteria were identified based on the growth characteristics of the colonies, Gram staining, and biochemical testing. The results of the analysis revealed the presence of 16 bacterial isolates, including Edwardsiella sp., Escherichia coli, and Vibrio sp. from dead fish, whereas Citrobacter sp, Providencia sp, and Vibrio sp were detected in diseased fish. In aquarium water, Escherichia coli, Citrobacter sp Proteus sp and Providencia sp. were detected. Betta fish are susceptible to suffer from diseases if the water quality is low since maintaining and enhancing the health of betta fish is highly dependent on water quality.